Indonesian tafsir: Development of definitions and shifting functions of tafsir - Chandra, Afzico Muhammad; Waehama, Muhammad Roflee (UIN Sunan Gunung Djati Bandung, 2025)
Tafsir, in its dynamics, does not only function as a medium for studying Allah's verses. There has been a shift in the function of interpretation to become a field for cultivating the interests of individuals, groups and even state governments. This shift in function occurs because tafsir has experienced a development in meaning; previously, tafsir had to be written by someone who met the requirements of a mufassir, but this was not strictly adhered to by tafsir writers from Indonesia. Through this article, various interests in various Indonesian interpretations are discussed, starting from the strengthening of ideology, politics by the government, highlighting communities, even interpretations being used as a means to criticize government policies, and so on. There are various forms of tafsir studied, ranging from the Al-Qur'an Encyclopedia, local language tafsir, to government-published translations of the Qur'an. Thus, interpretations that emerge from the Indonesian context are not only viewed as normative interpretations, but also as interpretations of interests or ideological interpretations.